A alfabetização/educação de surdos na história da educação do Espírito Santo - Rodrigues, Ednalva Gutierrez (2014)
This work integrates a research group developed by the line of research Education and Languages belonging to the Post-Graduation Program of the Espírito Santo State Federal University. It is about a historic research that aims at investigating the history of literacy of the deaf in the State of Espírito Santo, from 1950 to 1970, based on the initial thesis that education/literacy of the deaf children, in Espírito Santo, in that period, had the purpose to teach the national language through oralization, owing to the developmental project adopted by the Federal President, Juscelino Kubistchek. The work is based on Marc Bloch (2001) conceptions, by considering the History as the science of men in time, with the purpose to understand the human action according to the historic conditions of that time and on the contribution of the Bakhtin conceptions of language, specially, the text concept as enunciation, taking into consideration that each text/document brings in its central a history lived by subjects in a certain social and historical context. This way, from the analysis of school documents, journalistic texts, booklets, pedagogical materials and official documents, the work is structured in the sense of understanding the national context that gave rise to the first initiations of decentralization concerning the education of the deaf, culminating with the creation of special classes in several Brazilian states, including Espírito Santo. The repercussions, in local ambit, were analyzed from two axes. In the first one, the political aspects were analyzed, highlighting that the Government disclaimer favored the partnership between the public sphere and the private one in the configuration of the special classes, within the regular schools. The second one stood out that the Oral Method and the Perdoncini Method, which rooted the literacy process and aimed at teaching the country’s official language, regarding the oral modality, dialogued with the pedagogical and psychological conception of that time, making the process clearly educational. The work concludes that the period was marked by an educational project considered consistent and coherent with the postulates of that time, having in the responsible and polyphonic action of the Teacher Álpia Couto-Lenzi its main interlocutor.